Laser-induced breakdown spectroscopy determination of toxic metals in fresh fish - Ponce, L.V. (2016)
A method based on laser induced breakdown spectroscopy (LIBS) for monitoring lead and copper accumulation in edible fish, particularly “tilapia del Nilo” (Oreochromis niloticus) is presented. The capability of this analytical method is compared with results obtained by atomic absorption spectrometry. Detection limits by LIBS are 25 parts per million (ppm) for Pb and 100 ppm for Cu, values that are below the maximum permissible levels of some international standards. Application of LIBS detection allows the development of portable instruments for contamination control of edible fish.